If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-1 + 6i)(3 + -5i) = 0 Multiply (-1 + 6i) * (3 + -5i) (-1(3 + -5i) + 6i * (3 + -5i)) = 0 ((3 * -1 + -5i * -1) + 6i * (3 + -5i)) = 0 ((-3 + 5i) + 6i * (3 + -5i)) = 0 (-3 + 5i + (3 * 6i + -5i * 6i)) = 0 (-3 + 5i + (18i + -30i2)) = 0 Combine like terms: 5i + 18i = 23i (-3 + 23i + -30i2) = 0 Solving -3 + 23i + -30i2 = 0 Solving for variable 'i'. Factor a trinomial. (-3 + 5i)(1 + -6i) = 0Subproblem 1
Set the factor '(-3 + 5i)' equal to zero and attempt to solve: Simplifying -3 + 5i = 0 Solving -3 + 5i = 0 Move all terms containing i to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5i = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 5i = 0 + 3 5i = 0 + 3 Combine like terms: 0 + 3 = 3 5i = 3 Divide each side by '5'. i = 0.6 Simplifying i = 0.6Subproblem 2
Set the factor '(1 + -6i)' equal to zero and attempt to solve: Simplifying 1 + -6i = 0 Solving 1 + -6i = 0 Move all terms containing i to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -6i = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -6i = 0 + -1 -6i = 0 + -1 Combine like terms: 0 + -1 = -1 -6i = -1 Divide each side by '-6'. i = 0.1666666667 Simplifying i = 0.1666666667Solution
i = {0.6, 0.1666666667}
| 8[d+5]=12d-8 | | 3x-9=3(5-3x) | | 70-40+10x=12x+40-40 | | 3(x-3)-2(x+1)= | | 96t-16t^2-80=0 | | 5x+5=-115 | | 4+5x+9=7x-1 | | 4x^2-7x+11=9x+4 | | 0.75m+3=9 | | 2x-4(3-x)=7x+5 | | 5a-(2-a)=2a-14 | | 32t+-12=3t+42 | | 4[a+3]=2a+62 | | 24513465134+134613461= | | 19+t=-133 | | -14=w+3 | | 7z+14=5z+29 | | 18n=13 | | H=90-5t^2 | | 12=-4t | | 4+5x+9=7x+1 | | 8x+2=-6+3x+23 | | x^4+2x^2-36=0 | | (4x+5y)+(x+7y)= | | 1.5-0.04x=1.5 | | (x^2)-(2x)+(2)=0 | | 8+2=-6+3x+23 | | 5x+11y=-13 | | 7(v+3)-4v=27 | | 3x-9=12x-13 | | (X^2)-216=0 | | x^2-8x-42=-2x-2 |